Front cover: Pathoproteomic profiling of the skeletal muscle matrisome in dystrophinopathy associated myofibrosis. Issue 2 (15th January 2016) - Holland, Ashling; Murphy, Sandra; Dowling, Paul; Ohlendieck, Kay
Abstract : DOI:10.1002/pmic.201500158 Cover outlines the main findings from the proteomic profiling of muscular dystrophy‐related myofibrosis, which is characterised by the drastic increase in collagens, proteoglycans and the matricellular protein periostin in the extracellular matrix of dystrophin‐deficient muscle tissue. For details, see the review by Ashling Holland et al. on page 345.